2021
DOI: 10.1172/jci.insight.137245
|View full text |Cite
|
Sign up to set email alerts
|

Direct conversion of osteosarcoma to adipocytes by targeting TNIK

Abstract: Osteosarcoma (OS) is an aggressive mesenchymal tumor for which no molecularly targeted therapies are available. We have previously identified TRAF2- and NCK-interacting protein kinase (TNIK) as an essential factor for the transactivation of Wnt signal target genes and shown that its inhibition leads to eradication of colorectal cancer stem cells. The involvement of Wnt signaling in the pathogenesis of OS has been implicated. The aim of the present study was to examine the potential of TNIK as a therapeutic tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 73 publications
0
12
0
1
Order By: Relevance
“…It has been reported that GPR110 ( ADGRF1 ) can induce cell cycle arrest and chemoresistance in breast cancer [ 32 ]. TNIK appeared to be an essential factor for WNT signaling and stemness in colorectal cancer [ 33 ] and might be responsible for chemoresistance in osteosarcoma [ 34 ]. However, the 4-gene signature, consisting of GPR110 , TNIK , WDR4, and BRCA1 , showed no association with nCRT response in any of the validation cohorts of LARC biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that GPR110 ( ADGRF1 ) can induce cell cycle arrest and chemoresistance in breast cancer [ 32 ]. TNIK appeared to be an essential factor for WNT signaling and stemness in colorectal cancer [ 33 ] and might be responsible for chemoresistance in osteosarcoma [ 34 ]. However, the 4-gene signature, consisting of GPR110 , TNIK , WDR4, and BRCA1 , showed no association with nCRT response in any of the validation cohorts of LARC biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have shown that modulation of some specific RNAs could result in activation or inactivation of the Wnt/β-catenin signaling pathway in human cancers, including gastrointestinal cancers [21] , prostate cancer [22] , breast cancer [11] and many others [23] , [24] . Recently, two reports have also revealed the activated status of Wnt/β-catenin signaling pathway in Osteosarcoma [25] , [26] . Our results from transwell assay, migration assay, and invasion assay confirmed that down-regulation of BAIAP2L2 inhibited cell migration/invasion and induced the inactivation of Wnt /β-catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Repressing the signaling pathways related to the maintenance of CSCs (see Table 1) resulted in the slowdown of tumor growth and inhibition of the metastatic process [105][106][107][108][109][110][111][112][113][114][115][116] . As previously mentioned, Wnt/βcatenin appeared crucial for the maintenance of CSCs and its attenuation by using tankyrase inhibitor, or tegavivint was associated with a decrease in both CSC numbers and tumor progression [105,106] .…”
Section: Therapeutic Targeting Of Cancer Stem-like Cells In Osteosarcomamentioning
confidence: 99%
“…Drugs targeting transcription factors (e.g., STAT-3 and STAT5) controlling the development of CSCs may also be used to improve the therapeutic approaches to osteosarcoma [75,111,112] . Activation of hormone signaling can reduce stemness in osteosarcoma, as shown by the activation of estrogen receptor alpha by decitabine [113] . Most cytokineinduced signaling pathways result in the translocation of transcription factors which modulate the transcription of target genes.…”
Section: Therapeutic Targeting Of Cancer Stem-like Cells In Osteosarcomamentioning
confidence: 99%
See 1 more Smart Citation